PENGARUH CUSTOMER SATISFACTION DAN JOB SATISFACTION TERHADAP KINERJA KARYAWAN STUDI PADA BANK BRI PERSERO CABANG TERNATE - Meydina Nurul Kinanti; Adnan Rajak; Ikrima M. Mustafa (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of customer satisfaction and job satisfaction on employee performance in the study at Bank BRI Persero, Ternate Branch. This type of research uses a quantitative approach. The population in the study on the effect of customer satisfaction and job satisfaction on employeeperformance in the study at Bank BRI Persero Ternate Branch. The number of samples used as many as 129 respondents. The data in this study are primary data and secondary data sourced from questionnaires, interviews and observations which were distributed directly to Bank BRI Persero Ternate Branch, as well as using the SPSS 22 program assistance tool. The results of this study indicate that partially the Customer Statisfaction variable has a positive and significant effect on employee performance and the Job Statisfaction variable has a positive and significant effect on employee performance. Meanwhile, the variables of Customer Statisfaction and Job Statisfaction have a positive and significant effect on the performance of the employees of Bank BRI Persero Ternate Branch. Keywords: Customer Statisfaction, Job Statisfaction and Employee Performanc